The influence of subjective socioeconomic status on executive functions in middle-aged and older adults - WONG, Yu Ping (Institutional Knowledge at Singapore Management University, 2022)
Subjective socioeconomic status (SES) has been shown to influence both psychological and biological outcomes. However, less is known about whether its influence extends to cognitive outcomes. We examined the relation between subjective SES and executive functions (EF)—a set of cognitive control processes—and its underlying mechanisms. By analyzing a nationally representative cohort of middle-aged and older adults (age 40–80) from the MIDUS 2 National Survey and Cognitive Project, we tested a serial mediation model with sense of control and health as sequential mediators. Using structural equation modeling, we found that subjective SES is indirectly related to EF via sense of control and health, above and beyond objective SES and other key covariates. Our study highlights one of the possible biopsychosocial mechanisms that underlies the relation between status-related subjective perceptions of inequalities and executive functioning skills in middle and late adulthood.